Implementasi job order costing pada Penjahit Citra di Sumba Timur - Melanium Gloria Nicolas; Norman Duma Sitinjak (University of Merdeka Malang, 2023)
Micro, Small and Medium Enterprises is a general term in the economic world of productive businesses owned by individuals and business entities that have met the criteria as micro enterprises. One of the businesses that fall into the criteria of a small business is a sewing business. The formulation of the problem from this research is